Engagement of private providers in immunization in the Western Pacific region. Issue 32 (6th August 2018) - Amarasinghe, Ananda; Davison, Laura; Diorditsa, Sergey
Abstract: Financial sustainability of national immunization programmes (NIPs) in the Western Pacific is a growing concern. In the face of decreasing donor support for public immunization programmes, the role of private providers is becoming growingly important in attaining and sustaining programme achievements. Two-thirds of Member States in the Region have engaged the private sector in their immunization programmes, however little is known about the range and type of engagement. A survey was conducted in 2016 to map the scope and characteristics of private provider involvement, in order to inform guidance for decision makers. 14 countries participated, with responses from NIPs, national regulatory agencies, national immunization technical advisory groups (NITAGs), and private providers (defined as any entity other than the government). Findings revealed that most countries have policies and regulations concerning private providers, but 50% of private provider respondents were unaware that such policies are available. In most countries private providers' contribution is limited to less than 10% of the total target population. Private providers in only 6 countries surveyed follow the vaccination schedule recommended by the NIP, with demand by vaccine recipients being the main cause of deviation. A majority (>70%) of private provider respondents believe that clients seeks their services not because of perception of quality, but to access new vaccines unavailable through the NIP. Private providers in all countries received vaccines from the NIP at no cost, for which they only charge clients a service fee. The majority of private providers received training from the NIP, whereas only around 25% of them received training from their own institutions. Private providers from 11 countries share EPI performance data and adverse events following immunization, however, NIPs perceive this data as suboptimal. Private providers have a limited role in decision making processes, such as NITAGs. Further effective engagement of private sector providers has the potential to improve overall efficiency of immunization service delivery.